Fiddlers : a novel of the 87th Precinct - McBain, Ed, 1926- (Orlando, Fla. Harcourt, 2005)
Detective Steve Carella and his colleagues at the 87th Precinct struggle to discover a link between the apparently random victims of a profile-resistant serial killer who has murdered five times in two weeks.
"An Otto Penzler book."
Keywords: Carella, Steve (Fictitious character) -- Fiction; 87th Precinct (Imaginary place) -- Fiction; Police -- United States -- Fiction; Shooters of firearms -- Fiction; Serial murders -- Fiction; Mystery fiction